Electrical Stress Distribution of Ester Oil Transformers Under Lightning Impulse Conditions - Agarwal, Ritika (My University, 2019)
Ester oils are becoming potential substitutes for mineral oil, due to their better biodegradability and high flash and high fire point compared to conventionally used transformer oil. The high affinity of ester fluids for moisture helps in enhancing the life of the paper insulation and hence that of the transformer. Due to higher permittivity of both natural ester and synthetic ester than mineral oil it is advantage for the electrical field distribution in the power transformer. With the increase in its popularity, it becomes important to understand complete insulating properties of natural esters and synthetic ester and also their impact on transformer insulation design. Compared to sphere- sphere configuration, point sphere configuration is more dangerous in transformers. Most of the failures that happen in transformers are due to non-uniformity in the field experienced by insulation which leads to failure of insulation system inside the transformers. Due to this reason, performance of two natural esters and a mineral oil is examined under lightning impulse using the point-sphere using vertical electrode configuration. The impact of both positive and negative polarities is explored. The obtained data is further analyzed by Weibull distribution (3-parameter Weibull) to predict the 1% failure probability breakdown voltage for each type of oil and by using FEM technique electrical stress analysis is performed resulting in calculation of utilization factor. Further, from time to breakdown, velocity of streamer is calculated under both positive and negative polarity. Above all analysis is performed for small oil electrode gaps. For long oil gaps stress analysis using ElecNet is performed. In this dielectric strength of the insulation structure between HV lead connection to tap winding of 36MVA, 220/6.9kV power transformer is evaluated. To reduce the complexity of the full model, quarter model of winding, tank and core assembly is considered. Only single phase winding is considered for analysis. HV winding is modeled as discs with paper covering and applied with AC switching impulse test voltages. The complete tap and LV windings are assumed as single cylinder windings. Further for impulse voltage distribution testing, laboratory scale single phase transformer model is fabricated in which continuous double disc winding is incorporated. Due to change in permittivity of oil experiments are performed for both mineral oil and natural ester oil.
Keywords: Transformer; Ester oil; Electrical Stress Distribution; Impulse Conditions